2002
DOI: 10.1074/jbc.m107571200
|View full text |Cite
|
Sign up to set email alerts
|

Discoidin Domain Receptor 2 Regulates Fibroblast Proliferation and Migration through the Extracellular Matrix in Association with Transcriptional Activation of Matrix Metalloproteinase-2

Abstract: Discoidin domain receptor 2 (DDR2) is a tyrosine kinase receptor expressed in mesenchymal tissues, the ligand of which is fibrillar collagen. We have compared DDR2 signaling in skin fibroblasts derived from DDR2 ؊/؊ and DDR2 ؉/؊ mice. Proliferation of DDR2 ؊/؊ fibroblasts was significantly decreased compared with DDR2 ؉/؊ cells. DDR2 ؊/؊ fibroblasts exhibited markedly impaired capacity to migrate through a reconstituted basement membrane (Matrigel) in response to a chemotactic stimulus, which correlated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
177
3
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(193 citation statements)
references
References 48 publications
(48 reference statements)
8
177
3
1
Order By: Relevance
“…Activation of Eph family receptors by their cell-surface ligands was also reported to require at least 1 h for maximum receptor phosphorylation (69). In addition, tyrosine phosphorylation of discoidin domain receptor-2 caused by type I collagen was reported to take place at 30 min after stimulation and to last for 120 min (70,71), showing a time course very similar to that for our present observations. Thus, the time course of signal activation seems to be varied among the combination of ligands and their receptors, although the precise molecular mechanism for this variation is not known.…”
Section: Discussionsupporting
confidence: 77%
“…Activation of Eph family receptors by their cell-surface ligands was also reported to require at least 1 h for maximum receptor phosphorylation (69). In addition, tyrosine phosphorylation of discoidin domain receptor-2 caused by type I collagen was reported to take place at 30 min after stimulation and to last for 120 min (70,71), showing a time course very similar to that for our present observations. Thus, the time course of signal activation seems to be varied among the combination of ligands and their receptors, although the precise molecular mechanism for this variation is not known.…”
Section: Discussionsupporting
confidence: 77%
“…It was assumed that the buildup of ECM depends on fibroblast function (45,46) in the same manner that capillary sprout motion depends on the motion of the capillary tips; that is, the velocity v of the ECM density is given by…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, previous studies have shown a significant prognostic value for MMP-2 in NSCLC (41). Interestingly, expression and activation of MMP-2 and MMP-9 are complexly controlled by upstream signaling pathways, such as MAPKs (42), integrin (43), and discoidin domain receptor 2 (44). The transcription of MMP-2 and MMP-9 genes is regulated by upstream regulatory sequences, including NFkB-, AP-1-, and Ets-1-binding sites (9).…”
Section: Discussionmentioning
confidence: 99%